ZIF-MOG derived composite carbon nanofiber catalyst as well as preparation method and application thereof

Through the preparation of ZIF-MOG-derived composite nanocarbon fiber catalyst, the problem of low oxygen reduction and oxygen precipitation reaction efficiency in zinc-air batteries is solved, and more efficient electrochemical performance and more stable cycle performance are achieved.

CN119695176AActive Publication Date: 2025-03-25XINYU UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411840508.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-25
Estimated Expiration
2044-12-13

AI Technical Summary

Technical Problem

During the charging and discharging process of zinc-air batteries, the slow kinetics of oxygen reduction (ORR) process and the high potential of oxygen precipitation reaction (OER) limit their industrialization development.

Method used

ZIF-MOG-derived composite nanocarbon fiber catalyst is used to form a composite catalyst by combining ZIF-67 with metal organic gel (MOG) and electrospinning technology. The nanofibers are prepared by electrospinning, followed by high-temperature carbonization treatment to form a composite catalyst.

Benefits of technology

The kinetic process of the oxygen reduction reaction is improved, and the overpotential of the oxygen precipitation reaction is reduced, the dual-function activity and stability of the catalyst is enhanced, and the cycle life of the zinc-empty battery is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119695176A_ABST
    Figure CN119695176A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of batteries, and provides a ZIF-MOG derived composite carbon nanofiber catalyst as well as a preparation method and application thereof. The method comprises the following steps: reacting dimethylimidazole, metal salt and an organic solvent to obtain ZIF-67; the preparation method comprises the following steps: mixing metal salt, a nitrogen-containing component, resorcinol and water, sequentially adding formaldehyde and ammonia water, and reacting to form metal organic gel; the preparation method comprises the following steps: mixing ZIF-67, MOG, a nanofiber polymer and a solvent, carrying out electrostatic spinning, and then carrying out high-temperature carbonization. Codoping of ZIF-67 and MOG on microscopic nanofibers is achieved through electrostatic spinning, the structural performance advantages of ZIF-67 and MOG are brought into play, and the specific surface area and the electronic conductivity of the material are greatly improved; different structures and active centers synergistically improve the conductivity, the electrochemical stability, the thermal stability and the difunctional catalytic activity of oxidation reduction of the material, and the power density and the energy efficiency of the battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of batteries, and in particular to a ZIF-MOG derived composite nano-carbon fiber catalyst and a preparation method and application thereof. Background Art

[0002] Zinc-air battery (ZAB) is a primary battery with oxygen in the air as the positive electrode active material, zinc as the negative electrode, and neutral or alkaline solution as the electrolyte. It has high theoretical specific capacity density, safety and pollution-free, simple structure, abundant zinc resources, low price and other advantages, and has received much attention in the field of new energy storage. However, during the charge and discharge process of zinc-air battery, the slow kinetics of oxygen reduction (ORR) process and the high potential of oxygen evolution reaction (OER) restrict its industrial development. Therefore, it is particularly important to select a suitable positive bifunctional catalyst to increase the speed of ORR reaction and reduce the overpotential of OER reaction.

[0003] Zeolitic imidazole framework (ZIF-67) has the advantages of high specific surface area, rich porosity, easy functionalization, high crystallinity, etc. Its high porosity provides a lot of space and channels for material adsorption, storage and transmission. At the same time, the metal ions and organic ligands (dimethylimidazole) of ZIF-67 are connected by strong coordination bonds, and its unique structure and electronic properties show excellent ORR catalytic activity in catalytic reactions.

[0004] Metal organic gel (MOG) is a new type of polymer composite material, which has been widely studied in the field of electrocatalysis due to its high specific surface area, good thermal stability, controllability, and high yield. MOG has a three-dimensional network structure, which gives it a high specific surface area and abundant nanopores. Thanks to this structure, it is very easy to dope. According to different catalytic reaction requirements, catalytic materials with specific composition and structure can be prepared, showing excellent controllability and catalytic activity.

[0005] PAN-based nanocarbon fibers prepared by electrospinning have the characteristics of large specific surface area and rich porosity, which are conducive to accelerating the transmission efficiency of electrons. Therefore, by integrating composite electrode materials into highly conductive nanocarbon fibers through electrospinning technology, it is possible to achieve a stable, orderly and uniform distribution of multiple catalytic active centers. It is of great value to utilize the synergistic catalytic effect of the microscopic active centers of each material to improve the charge exchange efficiency and stability of the composite electrode material during the redox cycle, thereby improving its electrochemical performance. Summary of the invention

[0006] The purpose of the present invention is to provide a ZIF-MOG derived composite nano-carbon fiber catalyst and a preparation method and application thereof in order to overcome the deficiencies of the prior art.

[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0008] The present invention provides a method for preparing a ZIF-MOG derived composite nanocarbon fiber catalyst, comprising the following steps:

[0009] 1) mixing dimethylimidazole, a metal salt and an organic solvent and reacting them to obtain ZIF-67;

[0010] 2) mixing the metal salt, the nitrogen-containing component, resorcinol and water to obtain a mixed solution, and sequentially adding formaldehyde and ammonia water to the mixed solution to react and form a metal organic gel;

[0011] 3) mixing ZIF-67, metal organic gel, nanofiber polymer and solvent to obtain a spinning solution;

[0012] 4) The spinning solution is electrospun and dried sequentially to obtain nanofibers;

[0013] 5) The nanofibers are sequentially subjected to high temperature carbonization and refinement treatment to obtain a ZIF-MOG derived composite nanocarbon fiber catalyst.

[0014] Preferably, the organic solvent in step 1) is ethanol, N,N-dimethylformamide or methanol, and the metal salt is iron salt, cobalt salt, nickel salt, copper salt or zinc salt;

[0015] The molar ratio of the metal salt to dimethylimidazole is 1:8-80, and the molar ratio of dimethylimidazole to the organic solvent is 1:16-160;

[0016] The reaction temperature is 15-80° C., and the reaction time is 2-48 hours.

[0017] Preferably, the metal salt in step 2) is an iron salt, a cobalt salt, a nickel salt, a copper salt or a zinc salt; the nitrogen-containing component is peptone, melamine, urea or chitosan;

[0018] The reaction time is 5 to 120 minutes, the reaction temperature is 30 to 140° C. Ammonia water is added to make the pH value of the system 7 to 14.

[0019] Preferably, in step 2), the molar ratio of the metal salt, the nitrogen-containing component and resorcinol is 1:1-10:20-200, the molar ratio of resorcinol to formaldehyde is 1:1-3, and the molar ratio of resorcinol to water is 1:25-30.

[0020] Preferably, in step 3), the nanofiber polymer comprises polyacrylonitrile, polyvinyl pyrrolidone, polyvinyl alcohol, polystyrene or polymethyl methacrylate; the molecular weight of polyacrylonitrile is 50,000 to 300,000, and the solvent comprises water, N,N-dimethylformamide, methanol or ethanol;

[0021] The mixing temperature is 20-100° C., and the mixing time is 6-96 hours.

[0022] Preferably, in step 3), the mass ratio of ZIF-67 to metal organic gel is 1-100:1-100, and the mass ratio of the total mass of ZIF-67 and metal organic gel to the nanofiber polymer is 1-10:1-10.

[0023] Preferably, the process parameters of the electrospinning in step 4) are: the voltage of the needle is 5 to 50 kV, the injection rate is 0.1 to 10 mL / h, the collection speed is 200 to 1000 rpm, the round-trip distance is 60 to 180 mm, the spinning temperature is 10 to 50 ° C, and the spinning humidity is 10 to 60% RH; the drying temperature is 40 to 100 ° C, and the drying time is 2 to 48 h.

[0024] Preferably, the temperature of the high-temperature carbonization in step 5) is 650-1200°C, the time of the high-temperature carbonization is 1-12h, and the heating rate of the high-temperature carbonization is 2-15°C / min; the high-temperature carbonization is carried out under a protective gas atmosphere, and the flow rate of the protective gas is 10-200mL / min.

[0025] The invention also provides a ZIF-MOG derived composite nano-carbon fiber catalyst prepared by the preparation method.

[0026] The present invention also provides the use of the ZIF-MOG derived composite nano-carbon fiber catalyst in a battery, wherein the battery is a battery in which oxygen participates in the cathode reaction.

[0027] The beneficial effects of the present invention include the following:

[0028] 1) The ZIF-MOG-derived composite carbon fiber material prepared by the present invention has excellent electrocatalytic activity and stability. The present invention uses electrospinning technology to realize the coordinated construction of ZIF-MOG-derived composite carbon fiber material by ZIF-67 and MOG. The multi-active center synergistic catalysis accelerates the kinetic process of oxygen reduction and reduces the overpotential of the oxygen evolution reaction. After long-term charge and discharge cycles, the voltage range remains stable without obvious attenuation. The ZIF-MOG-derived composite carbon fiber material prepared by the present invention has good bifunctional catalytic activity and stability, green and environmental protection, and has broad development prospects.

[0029] 2) The present invention utilizes the chemical reaction between metal ions and organic ligands to prepare the precursor ZIF-67 with excellent performance and high porosity in a relatively simple manner. The ZIF-67 material has the advantages of excellent electrochemical stability and the like. The present invention utilizes the condensation reaction between resorcinol and formaldehyde to prepare MOG with large yield and excellent performance. At the same time, its electrocatalytic activity is further improved by doping metal ions and nitrogen sources.

[0030] 3) The present invention uses electrospinning to achieve co-doping of ZIF-67 and MOG on microscopic nanofibers, giving full play to their respective structural performance advantages, greatly improving the specific surface area and electronic conductivity of the material, and different structures and active centers synergistically improve the conductivity, electrochemical stability, thermal stability and redox bifunctional catalytic activity of the material itself, thereby further improving the power density and energy efficiency of batteries with oxygen involved in the cathode reaction. At the same time, during the high-temperature carbonization process of nanofibers, the high-temperature decomposition of urea, chitosan, and peptone supplements the nitrogen source for the catalyst itself, further improving the catalytic activity of the ZIF-MOG-derived composite carbon fiber material itself.

[0031] 4) The electrospinning technology of the present invention has the advantages of simple equipment operation, easy availability of materials, extremely low operating risk factor, high production efficiency, diverse collection methods, high equipment flexibility, small footprint, and easy satisfaction of experimental conditions. By adjusting parameters, nanofibers with higher fineness can be easily obtained, and it is also convenient to be compounded with other materials, which has great advantages.

[0032] 5) The present invention gives full play to the performance advantages of ZIF-67 and MOG, connects the two in series by using PAN-based nanocarbon fibers, optimizes the spatial distribution of ZIF-67 and MOG particles, and exposes more electrocatalytic active sites. The presence of nanofibers can also improve the conductivity of the catalyst itself, thereby further improving the electrocatalytic activity of the catalyst. The present invention can solve the problems of insufficient catalytic activity and poor long-term cycle stability of single ZIF-67 and MOG derivative materials, and is expected to further solve the problems of low surface activity and insufficient electrocatalytic activity of electrode materials at the positive electrode of the battery where oxygen participates in the cathode reaction in the prior art. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 ORR and LSV polarization curves of ZMCF-1 of Example 1, ZIF-67 and Pt / C of Comparative Example 1 in 0.1 mol / L KOH solution;

[0034] Figure 2 OER polarization curves of ZMCF-1 of Example 1, ZIF-67 of Comparative Example 1, and RuO2 in 1 mol / L KOH solution;

[0035] Figure 3 The discharge polarization curve and power density diagram of the zinc-air battery assembled with ZMCF-1 and Pt / C as cathode catalysts in Example 1, respectively;

[0036] Figure 4 The ZMCF-1 of Example 1 was used as the cathode catalyst to assemble the zinc-air battery and the Pt / C-RuO2 battery at 10 mA / cm 2 Constant current charge and discharge curve under ;

[0037] Figure 5 ORR and LSV polarization curves of ZMCF-2 and Pt / C in 0.1 mol / L KOH solution of Example 2;

[0038] Figure 6 This is the OER polarization curve of ZMCF-2 and RuO2 in Example 2 in 1 mol / L KOH solution. DETAILED DESCRIPTION

[0039] The present invention provides a method for preparing a ZIF-MOG derived composite nanocarbon fiber catalyst, comprising the following steps:

[0040] 1) mixing dimethylimidazole, a metal salt and an organic solvent and reacting them to obtain ZIF-67;

[0041] 2) mixing the metal salt, the nitrogen-containing component, resorcinol and water to obtain a mixed solution, and sequentially adding formaldehyde and ammonia water to the mixed solution to react and form a metal organic gel;

[0042] 3) mixing ZIF-67, metal organic gel, nanofiber polymer and solvent to obtain a spinning solution;

[0043] 4) The spinning solution is electrospun and dried sequentially to obtain nanofibers;

[0044] 5) The nanofibers are sequentially subjected to high temperature carbonization and refinement treatment to obtain a ZIF-MOG derived composite nanocarbon fiber catalyst.

[0045] In the present invention, the organic solvent in step 1) is preferably ethanol, N,N-dimethylformamide or methanol, and the metal salt is preferably an iron salt, a cobalt salt, a nickel salt, a copper salt or a zinc salt;

[0046] The molar ratio of the metal salt to dimethylimidazole is preferably 1:8-80, more preferably 1:12-70, more preferably 1:20-60, and the molar ratio of dimethylimidazole to the organic solvent is preferably 1:16-160, more preferably 1:25-140, more preferably 1:35-100;

[0047] The reaction temperature is preferably 15 to 80° C., more preferably 25 to 70° C., and more preferably 35 to 60° C.; the reaction time is preferably 2 to 48 h, more preferably 5 to 40 h, and more preferably 10 to 30 h.

[0048] In the present invention, in step 1), the mixing is preferably that dimethylimidazole is first dissolved in an organic solvent to obtain a mixed solution, and then the metal salt is added to the mixed solution; the dissolution time is preferably 5 to 60 minutes, more preferably 10 to 50 minutes, and more preferably 20 to 40 minutes; after the reaction is completed, impurities are removed and dried in sequence to obtain ZIF-67; the impurity removal method is preferably centrifugal washing; the drying temperature is preferably 40 to 200°C, more preferably 50 to 180°C, and more preferably 80 to 150°C; the drying time is preferably 8 to 72 hours, more preferably 10 to 70 hours, and more preferably 15 to 65 hours; and the drying is carried out in a blast drying oven or a vacuum drying oven.

[0049] In the present invention, the dimethylimidazole (2-MIM) in step 1) is an organic ligand, the metal salt provides metal ions, and the organic solvent provides a reaction medium. During the reaction, the metal ions combine with the organic ligand to synthesize ZIF-67.

[0050] In the present invention, the metal salt in step 2) is preferably an iron salt, a cobalt salt, a nickel salt, a copper salt or a zinc salt; the nitrogen-containing component is preferably peptone, melamine, urea or chitosan;

[0051] The reaction time is preferably 5 to 120 min, more preferably 10 to 110 min, more preferably 20 to 100 min, the reaction temperature is preferably 30 to 140° C., more preferably 40 to 100° C., more preferably 50 to 80° C.; ammonia water is added to make the pH value of the system preferably 7 to 14, more preferably 8 to 13, more preferably 9 to 12.

[0052] In the present invention, the molar ratio of the metal salt, the nitrogen-containing component and resorcinol in step 2) is preferably 1:1-10:20-200, more preferably 1:2-9:30-180, more preferably 1:3-7:40-160, the molar ratio of resorcinol to formaldehyde is preferably 1:1-3, more preferably 1:1.5-2.5, more preferably 1:2, and the molar ratio of resorcinol to water is preferably 1:25-30, more preferably 1:26-28, more preferably 1:27.

[0053] In the present invention, after the reaction in step 2) is completed, drying and grinding are carried out in sequence to obtain a metal organic gel; the drying temperature is preferably 40 to 135° C., more preferably 60 to 120° C., more preferably 80 to 110° C., and the drying time is preferably 2 to 10 days, more preferably 3 to 9 days, and more preferably 5 to 8 days.

[0054] In the present invention, the nanofiber polymer in step 3) preferably comprises polyacrylonitrile (PAN), polyvinyl pyrrolidone (PVP), polyvinyl alcohol (PVA), polystyrene (PS) or polymethyl methacrylate (PMMA); the molecular weight of polyacrylonitrile is preferably 50,000 to 300,000, more preferably 80,000 to 250,000, and more preferably 100,000 to 200,000, and the solvent preferably comprises water, N,N-dimethylformamide, methanol or ethanol;

[0055] The mixing temperature is preferably 20-100° C., more preferably 30-90° C., more preferably 40-80° C., and the mixing time is preferably 6-96 h, more preferably 16-90 h, more preferably 24-80 h; and the mixing is preferably magnetic stirring or ultrasonic oscillation.

[0056] In the present invention, the mass ratio of ZIF-67 and metal organic gel in step 3) is preferably 1-100:1-100, further preferably 1-80:1-80, and more preferably 1-40:1-40; the mass ratio of the total mass of ZIF-67 and metal organic gel to the nanofiber polymer is preferably 1-10:1-10, further preferably 1-8:1-8, and more preferably 1-5:1-5.

[0057] In the present invention, the process parameters of the electrospinning in step 4) are: the voltage of the needle is preferably 5-50 kV, more preferably 10-40 kV, more preferably 15-35 kV, the injection rate is preferably 0.1-10 mL / h, more preferably 0.5-9 mL / h, more preferably 1-8 mL / h, the collection speed is preferably 200-1000 rpm, more preferably 300-800 rpm, more preferably 400-700 rpm, the round trip distance is preferably 60-180 mm, more preferably The spinning temperature is preferably 10-50°C, more preferably 15-40°C, more preferably 20-30°C, and the spinning humidity is preferably 10-60%RH, more preferably 20-50%RH, more preferably 30-40%RH; the drying temperature is preferably 40-100°C, more preferably 50-90°C, more preferably 60-80°C, and the drying time is preferably 2-48h, more preferably 5-40h, more preferably 12-35h.

[0058] In the present invention, the temperature of the high temperature carbonization in step 5) is preferably 650-1200°C, more preferably 750-1100°C, and more preferably 850-1000°C. The time of high temperature carbonization is preferably 1-12h, more preferably 3-10h, and more preferably 5-8h. The heating rate of high temperature carbonization is preferably 2-15°C / min, more preferably 3-12°C / min, and more preferably 5-10°C / min. The high temperature carbonization is preferably carried out under a protective gas atmosphere, and the flow rate of the protective gas is preferably 10-200mL / min, more preferably 20-180mL / min, and preferably 50-150mL / min.

[0059] In the present invention, the refinement treatment in step 5) is grinding and high-energy ball milling.

[0060] The invention also provides a ZIF-MOG derived composite nano-carbon fiber catalyst prepared by the preparation method.

[0061] The present invention also provides the use of the ZIF-MOG derived composite nano-carbon fiber catalyst in a battery, wherein the battery is a battery in which oxygen participates in the cathode reaction.

[0062] In the present invention, the battery in which oxygen participates in the cathode reaction is preferably a zinc-air battery or a hydrogen-oxygen fuel cell.

[0063] The present invention utilizes electrostatic spinning technology to assemble the ZIF-67 particles and MOG particles prepared in the early stage in series through PAN-based carbon fibers, and then undergoes high-temperature carbonization and other treatments to obtain ZIF-MOG derived composite carbon fiber (ZMCF) materials. The specific process is: first, through the coordination self-assembly reaction of metal ions and organic ligands, deprotonation of organic ligands, coordination of metal ions and ligands, self-assembly to form a framework structure and other processes, ZIF-67 particles with excellent catalytic activity are synthesized; then, the polycondensation reaction of resorcinol and formaldehyde is utilized, and metal ions and nitrogen sources are added, and MOG particles with large yield and excellent performance are obtained through later aging. The above two substances are used as precursors to configure the spinning solution, and the composite carbon fiber material is prepared by electrostatic spinning. Finally, a high-temperature tubular furnace is used to perform high-temperature carbonization on the obtained electrode material in a protective gas atmosphere. The carbonization temperature is 650-1200°C. During the carbonization process, the nitrogen source is supplemented for the nanofibers themselves through the high-temperature decomposition of the nitrogen-containing components, and finally the obtained nano-carbon fibers are ground and subjected to high-energy ball milling. The ZIF-MOG-derived composite carbon fiber material prepared by the present invention has effectively improved its catalytic effect on oxygen reduction (ORR) and oxygen evolution (OER) reactions. From the charge and discharge tests of the battery assembled therefrom, its power density and long-term cycle capacity are improved, showing excellent bifunctional catalytic activity, and can be used for the preparation and research of battery positive electrode materials.

[0064] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0065] Example 1

[0066] Dissolve dimethylimidazole in N,N-dimethylformamide, mix and stir for 10 minutes, then pour cobalt nitrate hexahydrate into the mixed solution, mix and stir magnetically for 2 hours at 25°C, the molar ratio of cobalt nitrate hexahydrate to dimethylimidazole is 1:8, and the molar ratio of dimethylimidazole to N,N-dimethylformamide is 1:16. Then remove impurities by washing and centrifugation, and then put it into a vacuum drying oven at 80°C for 12 hours. When it cools to room temperature, ZIF-67 is obtained and ground for use.

[0067] Cobalt nitrate hexahydrate, resorcinol and peptone were dissolved in deionized water, and magnetic stirring was performed for 10 minutes to slowly dissolve the solid. Subsequently, formaldehyde was slowly added to the mixed solution, and the mixture was stirred for 0.5 hours. The molar ratio of cobalt nitrate hexahydrate, peptone and resorcinol was 1:1:20, the molar ratio of resorcinol to deionized water was 1:27, and the molar ratio of resorcinol to formaldehyde was 1:2. Ammonia water (AR, mass concentration of 26%) was slowly added to the mixed solution under 60°C water bath conditions, the pH value of the solution was adjusted to 7, and the reaction was stirred for 10 minutes to form an organic gel. Finally, the mixture was placed in a vacuum drying oven (vacuum degree of 133 Pa), vacuum dried at 80°C for 4 days, and the obtained solid was ground to obtain metal organic gel (MOG).

[0068] The ground ZIF-67, MOG and polyacrylonitrile (molecular weight of 100000) were added to N,N-dimethylformamide, the mass ratio of ZIF-67 to MOG was 1:1, and the mass ratio of the total mass of ZIF-67 and MOG to polyacrylonitrile was 1:2. The mixed solution was magnetically stirred at 20°C for 24 hours to obtain a uniformly mixed spinning solution.

[0069] 5 mL of spinning solution was placed in a 10 mL syringe, and electrospun nanofibers were obtained using electrospinning technology. The electrospinning parameters were: needle voltage of 13 kV, injection rate of 1 mL / h, collection speed of 450 rpm, round-trip distance of 120 mm, spinning temperature of 24 ° C, and spinning humidity of 10% RH. The electrospun nanofibers were placed in a vacuum drying oven and vacuum dried at 80 ° C for 12 h to obtain nanofibers.

[0070] The nanofibers were placed in a high-temperature tube furnace and carbonized at high temperature under inert gas N2 (N2 flow rate was 40 mL / min). 3 g of urea was placed in an ark at the air inlet of the tube furnace, and the temperature was raised to 800 ° C at a heating rate of 5 ° C / min, and carbonized at 800 ° C for 2 h. After carbonization, the obtained carbon nanocomposite material was ground and high-energy ball milled to obtain the ZIF-MOG-derived composite nanocarbon fiber catalyst (ZMCF-1).

[0071] Example 2

[0072] The mass ratio of ZIF-67 to MOG in Example 1 was changed to 1:20, and other conditions were the same as in Example 1 to obtain a ZIF-MOG derived composite nanocarbon fiber catalyst (ZMCF-2).

[0073] Example 3

[0074] Dissolve dimethylimidazole in N,N-dimethylformamide, mix and stir for 20 minutes, then pour ferric nitrate nonahydrate into the mixed solution, mix and stir magnetically for 6 hours at 18°C, the molar ratio of ferric nitrate nonahydrate to dimethylimidazole is 1:12, and the molar ratio of dimethylimidazole to N,N-dimethylformamide is 1:48. Then remove impurities by washing and centrifugation, and then dry in a vacuum drying oven at 40°C for 8 hours. When it cools to room temperature, ZIF-67 is obtained and ground for use.

[0075] Ferric nitrate nonahydrate, resorcinol and peptone were dissolved in deionized water, and magnetic stirring was performed for 15 minutes to slowly dissolve the solid. Subsequently, formaldehyde was slowly added to the mixed solution, and the mixture was stirred for 1 hour. The molar ratio of ferric nitrate nonahydrate, peptone and resorcinol was 1:3:30, the molar ratio of resorcinol to deionized water was 1:27, and the molar ratio of resorcinol to formaldehyde was 1:2. Ammonia water (AR, mass concentration of 27%) was slowly added to the mixed solution under 30°C water bath conditions, the pH value of the solution was adjusted to 8, and the reaction was stirred for 40 minutes to form an organic gel. Finally, the mixture was placed in a vacuum drying oven (vacuum degree of 133Pa), vacuum dried at 50°C for 6 days, and the obtained solid was ground to obtain metal organic gel (MOG).

[0076] The ground ZIF-67, MOG and polyvinyl pyrrolidone were added to N,N-dimethylformamide, the mass ratio of ZIF-67 to MOG was 1:3, and the mass ratio of the total mass of ZIF-67 and MOG to polyvinyl pyrrolidone was 1:4. The mixed solution was magnetically stirred at 35°C for 16 hours to obtain a uniformly mixed spinning solution.

[0077] 50 mL of spinning solution was placed in a 100 mL syringe, and electrospun nanofibers were obtained using electrospinning technology. The electrospinning parameters were: needle voltage of 11 kV, injection rate of 1.5 mL / h, collection speed of 350 rpm, round-trip distance of 100 mm, spinning temperature of 18 ° C, and spinning humidity of 20% RH. The electrospun nanofibers were placed in a vacuum drying oven and vacuum dried at 70 ° C for 8 h to obtain nanofibers.

[0078] The nanofibers were placed in a high-temperature tube furnace and carbonized at high temperature under inert gas N2 (N2 flow rate was 60 mL / min). 3 g of peptone was placed in an ark at the air inlet of the tube furnace, and the temperature was raised to 900 ° C at a heating rate of 5 ° C / min, and carbonized at 900 ° C for 4 hours. After carbonization, the obtained carbon nanocomposite material was ground and high-energy ball milled to obtain the ZIF-MOG-derived composite nanocarbon fiber catalyst (ZMCF-3).

[0079] Example 4

[0080] Dissolve dimethylimidazole in N,N-dimethylformamide, mix and stir for 25 minutes, then pour cobalt nitrate hexahydrate into the mixed solution, mix and stir magnetically for 8 hours at 30°C, the molar ratio of cobalt nitrate hexahydrate to dimethylimidazole is 1:14, and the molar ratio of dimethylimidazole to N,N-dimethylformamide is 1:64. Then remove impurities by washing and centrifugation, and then put it into a vacuum drying oven at 100°C and dry it for 14 hours. When it cools to room temperature, ZIF-67 is obtained and ground for use.

[0081] Dissolve cobalt nitrate hexahydrate, resorcinol and peptone in deionized water, stir magnetically for 15 minutes to slowly dissolve the solid, then slowly add formaldehyde to the mixed solution, mix and stir for 1.2 hours, the molar ratio of cobalt nitrate hexahydrate, peptone and resorcinol is 1:4:35, the molar ratio of resorcinol to deionized water is 1:27, and the molar ratio of resorcinol to formaldehyde is 1:2. Slowly add ammonia water (AR, mass concentration is 26%) to the mixed solution under 80°C water bath conditions, adjust the solution pH to 9, and stir the reaction for 50 minutes to form an organic gel, and finally put it into a vacuum drying oven (vacuum degree is 133Pa), vacuum dry it at 40°C for 7 days, and grind the obtained solid to obtain metal organic gel (MOG).

[0082] The ground ZIF-67, MOG and polyvinyl pyrrolidone were added to N,N-dimethylformamide, the mass ratio of ZIF-67 to MOG was 1:4, and the mass ratio of the total mass of ZIF-67 and MOG to polyvinyl pyrrolidone was 1:5. The mixed solution was magnetically stirred at 40°C for 20 hours to obtain a uniformly mixed spinning solution.

[0083] 100 mL of spinning solution was placed in a 150 mL syringe, and electrospun nanofibers were obtained using electrospinning technology. The electrospinning parameters were: needle voltage of 10 kV, injection rate of 1.2 mL / h, collection speed of 300 rpm, round-trip distance of 90 mm, spinning temperature of 16 ° C, and spinning humidity of 25% RH. The electrospun nanofibers were placed in a vacuum drying oven and vacuum dried at 50 ° C for 6 h to obtain nanofibers.

[0084] The nanofibers were placed in a high-temperature tube furnace and carbonized at high temperature under inert gas N2 (N2 flow rate was 80 mL / min). 3 g of chitosan was placed in an ark at the air inlet of the tube furnace, and the temperature was increased to 950°C at a heating rate of 6°C / min, and carbonized at 950°C for 5 hours. After carbonization, the obtained carbon nanocomposite material was ground and subjected to high-energy ball milling treatment to obtain the ZIF-MOG-derived composite nanocarbon fiber catalyst (ZMCF-4).

[0085] Example 5

[0086] Dissolve dimethylimidazole in N,N-dimethylformamide, mix and stir for 30 minutes, then pour zinc nitrate hexahydrate into the mixed solution, mix and stir magnetically for 10 hours at 35°C, the molar ratio of zinc nitrate hexahydrate to dimethylimidazole is 1:16, and the molar ratio of dimethylimidazole to N,N-dimethylformamide is 1:80. Then remove impurities by washing and centrifugation, and then put it into a vacuum drying oven at 110°C and dry it for 16 hours. When it cools to room temperature, ZIF-67 is obtained and ground for use.

[0087] Zinc nitrate hexahydrate, resorcinol and peptone were dissolved in deionized water, and magnetic stirring was performed for 15 minutes to slowly dissolve the solid. Subsequently, formaldehyde was slowly added to the mixed solution, and the mixture was stirred for 1.5 hours. The molar ratio of zinc nitrate hexahydrate, peptone and resorcinol was 1:5:40, the molar ratio of resorcinol to deionized water was 1:27, and the molar ratio of resorcinol to formaldehyde was 1:2. Ammonia water (AR, mass concentration of 27%) was slowly added to the mixed solution under 90°C water bath conditions, the pH value of the solution was adjusted to 9.5, and the reaction was stirred for 60 minutes to form an organic gel. Finally, it was placed in a vacuum drying oven (vacuum degree of 133Pa), vacuum dried at 90°C for 8 days, and the obtained solid was ground to obtain metal organic gel (MOG).

[0088] The ground ZIF-67, MOG and polyvinyl alcohol were added to N,N-dimethylformamide, the mass ratio of ZIF-67 to MOG was 4:1, and the mass ratio of the total mass of ZIF-67 and MOG to polyvinyl alcohol was 1:6. The mixed solution was magnetically stirred at 45°C for 28 hours to obtain a uniformly mixed spinning solution.

[0089] 200 mL of spinning solution was placed in a 400 mL syringe, and electrospun nanofibers were obtained using electrospinning technology. The electrospinning parameters were: needle voltage of 15 kV, injection rate of 0.8 mL / h, collection speed of 250 rpm, round-trip distance of 80 mm, spinning temperature of 14 ° C, and spinning humidity of 30% RH. The electrospun nanofibers were placed in a vacuum drying oven and vacuum dried at 40 ° C for 14 h to obtain nanofibers.

[0090] The nanofibers were placed in a high-temperature tube furnace and carbonized at high temperature under inert gas N2 (N2 flow rate was 100 mL / min). 3 g of chitosan was placed in an ark at the air inlet of the tube furnace, and the temperature was increased to 1050°C at a heating rate of 7°C / min, and carbonized at 1050°C for 6 hours. After carbonization, the obtained carbon nanocomposite material was ground and subjected to high-energy ball milling treatment to obtain the ZIF-MOG-derived composite nanocarbon fiber catalyst (ZMCF-5).

[0091] Example 6

[0092] Dissolve dimethylimidazole in N,N-dimethylformamide, mix and stir for 35 minutes, then pour cobalt nitrate hexahydrate into the mixed solution, mix and stir magnetically for 12 hours at 40°C, the molar ratio of cobalt nitrate hexahydrate to dimethylimidazole is 1:18, and the molar ratio of dimethylimidazole to N,N-dimethylformamide is 1:96. Then remove impurities by washing and centrifugation, and then put it into a vacuum drying oven at 120°C and dry it for 18 hours. When it cools to room temperature, ZIF-67 is obtained and ground for use.

[0093] Dissolve cobalt nitrate hexahydrate, resorcinol and peptone in deionized water, stir magnetically for 15 minutes to slowly dissolve the solid, then slowly add formaldehyde to the mixed solution, mix and stir for 1.8 hours, the molar ratio of cobalt nitrate hexahydrate, peptone and resorcinol is 1:6:45, the molar ratio of resorcinol to deionized water is 1:27, and the molar ratio of resorcinol to formaldehyde is 1:2. Slowly add ammonia water (AR, mass concentration is 26%) to the mixed solution under 100°C water bath conditions, adjust the solution pH to 10, and stir the reaction for 70 minutes to form an organic gel, and finally put it into a vacuum drying oven (vacuum degree is 133Pa), vacuum dry it at 100°C for 9 days, and grind the obtained solid to obtain metal organic gel (MOG).

[0094] The ground ZIF-67, MOG and polyvinyl alcohol were added to N,N-dimethylformamide, the mass ratio of ZIF-67 to MOG was 2:1, and the mass ratio of the total mass of ZIF-67 and MOG to polyvinyl alcohol was 1:7. The mixed solution was magnetically stirred at 50°C for 32 hours to obtain a uniformly mixed spinning solution.

[0095] 250 mL of spinning solution was placed in a 300 mL syringe, and electrospun nanofibers were obtained by electrospinning technology. The electrospinning parameters were as follows: needle voltage of 16 kV, injection rate of 0.5 mL / h, collection speed of 200 rpm, round trip distance of 70 mm, spinning temperature of 12 ° C, and spinning humidity of 35% RH. The electrospun nanofibers were placed in a vacuum drying oven and vacuum dried at 90 ° C for 16 h to obtain nanofibers.

[0096] The nanofibers were placed in a high-temperature tube furnace and carbonized at high temperature under inert gas N2 (N2 flow rate was 120 mL / min). 3 g of urea was placed in an ark at the air inlet of the tube furnace, and the temperature was raised to 1000°C at a heating rate of 8°C / min, and carbonized at 1000°C for 7 hours. After carbonization, the obtained carbon nanocomposite material was ground and subjected to high-energy ball milling treatment to obtain a ZIF-MOG-derived composite nanocarbon fiber catalyst (ZMCF-6).

[0097] Example 7

[0098] Dissolve dimethylimidazole in N,N-dimethylformamide, mix and stir for 40 minutes, then pour cobalt nitrate hexahydrate into the mixed solution, mix and stir magnetically for 14 hours at 45°C, the molar ratio of cobalt nitrate hexahydrate to dimethylimidazole is 1:20, and the molar ratio of dimethylimidazole to N,N-dimethylformamide is 1:112. Then remove impurities by washing and centrifugation, and then dry in a vacuum drying oven at 130°C for 20 hours. When it cools to room temperature, ZIF-67 is obtained and ground for use.

[0099] Cobalt nitrate hexahydrate, resorcinol and peptone were dissolved in deionized water, and magnetic stirring was performed for 15 minutes to slowly dissolve the solid. Subsequently, formaldehyde was slowly added to the mixed solution, and the mixture was stirred for 2 hours. The molar ratio of cobalt nitrate hexahydrate, peptone and resorcinol was 1:7:50, the molar ratio of resorcinol to deionized water was 1:27, and the molar ratio of resorcinol to formaldehyde was 1:2. Ammonia water (AR, mass concentration of 26%) was slowly added to the mixed solution under 110°C water bath conditions, the pH value of the solution was adjusted to 10.5, and the reaction was stirred for 80 minutes to form an organic gel. Finally, the mixture was placed in a vacuum drying oven (vacuum degree of 133 Pa), vacuum dried at 110°C for 10 days, and the obtained solid was ground to obtain metal organic gel (MOG).

[0100] The ground ZIF-67, MOG and polystyrene were added to N,N-dimethylformamide, the mass ratio of ZIF-67 to MOG was 1:8, and the mass ratio of the total mass of ZIF-67 and MOG to polystyrene was 1:8. The mixed solution was magnetically stirred at 55°C for 36 hours to obtain a uniformly mixed spinning solution.

[0101] 300 mL of spinning solution was placed in a 400 mL syringe, and electrospun nanofibers were obtained using electrospinning technology. The electrospinning parameters were: needle voltage of 17 kV, injection rate of 0.9 mL / h, collection speed of 500 rpm, round-trip distance of 60 mm, spinning temperature of 26 ° C, and spinning humidity of 40% RH. The electrospun nanofibers were placed in a vacuum drying oven and vacuum dried at 95 ° C for 18 h to obtain nanofibers.

[0102] The nanofibers were placed in a high-temperature tube furnace and carbonized at high temperature under inert gas N2 (N2 flow rate was 140 mL / min). 3 g of chitosan was placed in an ark at the air inlet of the tube furnace, and the temperature was increased to 1100°C at a heating rate of 9°C / min, and carbonized at 1100°C for 8 hours. After carbonization, the obtained carbon nanocomposite material was ground and subjected to high-energy ball milling treatment to obtain the ZIF-MOG-derived composite nanocarbon fiber catalyst (ZMCF-7).

[0103] Example 8

[0104] Dissolve dimethylimidazole in N,N-dimethylformamide, mix and stir for 44 minutes, then pour cobalt nitrate hexahydrate into the mixed solution, mix and stir magnetically for 16 hours at 50°C, the molar ratio of cobalt nitrate hexahydrate to dimethylimidazole is 1:22, and the molar ratio of dimethylimidazole to N,N-dimethylformamide is 1:128. Then remove impurities by washing and centrifugation, and then put it into a vacuum drying oven at 140°C and dry it for 22 hours. When it cools to room temperature, ZIF-67 is obtained and ground for use.

[0105] Dissolve cobalt nitrate hexahydrate, resorcinol and peptone in deionized water, stir magnetically for 15 minutes to slowly dissolve the solid, then slowly add formaldehyde to the mixed solution, mix and stir for 2.2 hours, the molar ratio of cobalt nitrate hexahydrate, peptone and resorcinol is 1:8:55, the molar ratio of resorcinol to deionized water is 1:27, and the molar ratio of resorcinol to formaldehyde is 1:2. Slowly add ammonia water (AR, mass concentration is 26%) to the mixed solution under 120℃ water bath conditions, adjust the solution pH to 12, and stir the reaction for 90 minutes to form an organic gel, and finally put it into a vacuum drying oven (vacuum degree is 133Pa), vacuum dry it at 120℃ for 3 days, and grind the obtained solid to obtain metal organic gel (MOG).

[0106] The ground ZIF-67, MOG and polystyrene were added to N,N-dimethylformamide, the mass ratio of ZIF-67 to MOG was 8:1, and the mass ratio of the total mass of ZIF-67 and MOG to polystyrene was 1:9. The mixed solution was magnetically stirred at 60°C for 40 hours to obtain a uniformly mixed spinning solution.

[0107] 600 mL of spinning solution was placed in a syringe with a capacity of 700 mL, and electrospun nanofibers were obtained using electrospinning technology. The electrospinning parameters were: needle voltage of 18 kV, injection rate of 0.7 mL / h, collection speed of 550 rpm, round-trip distance of 130 mm, spinning temperature of 28 ° C, and spinning humidity of 45% RH. The electrospun nanofibers were placed in a vacuum drying oven and vacuum dried at 100 ° C for 20 h to obtain nanofibers.

[0108] The nanofibers were placed in a high-temperature tube furnace and carbonized at high temperature under inert gas N2 (N2 flow rate was 160 mL / min). 3 g of peptone was placed in an ark at the air inlet of the tube furnace, and the temperature was increased to 700 ° C at a heating rate of 10 ° C / min, and carbonized at 700 ° C for 9 hours. After the carbonization, the obtained carbon nanocomposite material was ground and high-energy ball milled to obtain the ZIF-MOG-derived composite nanocarbon fiber catalyst (ZMCF-8).

[0109] Example 9

[0110] Dissolve dimethylimidazole in N,N-dimethylformamide, mix and stir for 46 minutes, then pour cobalt nitrate hexahydrate into the mixed solution, mix and stir magnetically for 17 hours at 55°C, the molar ratio of cobalt nitrate hexahydrate to dimethylimidazole is 1:24, and the molar ratio of dimethylimidazole to N,N-dimethylformamide is 1:144. Then remove impurities by washing and centrifugation, and then put it into a vacuum drying oven at 150°C and dry it for 24 hours. When it cools to room temperature, ZIF-67 is obtained and ground for use.

[0111] Dissolve cobalt nitrate hexahydrate, resorcinol and peptone in deionized water, stir magnetically for 15 minutes to slowly dissolve the solid, then slowly add formaldehyde to the mixed solution, mix and stir for 2.5 hours, the molar ratio of cobalt nitrate hexahydrate, peptone and resorcinol is 1:9:60, the molar ratio of resorcinol to deionized water is 1:27, and the molar ratio of resorcinol to formaldehyde is 1:2. Slowly add ammonia water (AR, mass concentration is 26%) to the mixed solution under 130°C water bath conditions, adjust the solution pH to 13, and stir the reaction for 100 minutes to form an organic gel, and finally put it into a vacuum drying oven (vacuum degree is 133Pa), vacuum dry it at 130°C for 2 days, and grind the obtained solid to obtain metal organic gel (MOG).

[0112] The ground ZIF-67, MOG and polymethyl methacrylate were added to N,N-dimethylformamide, the mass ratio of ZIF-67 to MOG was 10:1, and the mass ratio of the total mass of ZIF-67 and MOG to polymethyl methacrylate was 2:1. The mixed solution was magnetically stirred at 65°C for 42 hours to obtain a uniformly mixed spinning solution.

[0113] 700 mL of spinning solution was placed in a syringe with a capacity of 800 mL, and electrospun nanofibers were obtained using electrospinning technology. The electrospinning parameters were: needle voltage of 19 kV, injection rate of 1.8 mL / h, collection speed of 600 rpm, round-trip distance of 140 mm, spinning temperature of 30 ° C, and spinning humidity of 50% RH. The electrospun nanofibers were placed in a vacuum drying oven and vacuum dried at 85 ° C for 22 h to obtain nanofibers.

[0114] The nanofibers were placed in a high-temperature tube furnace and carbonized at high temperature under inert gas N2 (N2 flow rate was 180 mL / min). 3 g of peptone was placed in an ark at the air inlet of the tube furnace, and the temperature was increased to 650°C at a heating rate of 12°C / min, and carbonized at 650°C for 11 hours. After carbonization, the obtained carbon nanocomposite material was ground and subjected to high-energy ball milling treatment to obtain a ZIF-MOG-derived composite nanocarbon fiber catalyst (ZMCF-9).

[0115] Example 10

[0116] Dissolve dimethylimidazole in N,N-dimethylformamide, mix and stir for 50 minutes, then pour cobalt nitrate hexahydrate into the mixed solution, mix and stir magnetically at 80°C for 48 hours, the molar ratio of cobalt nitrate hexahydrate to dimethylimidazole is 1:80, and the molar ratio of dimethylimidazole to N,N-dimethylformamide is 1:160. Then remove impurities by washing and centrifugation, and then put it into a vacuum drying oven at 200°C and dry it for 72 hours. When it cools to room temperature, ZIF-67 is obtained and ground for use.

[0117] Cobalt nitrate hexahydrate, resorcinol and peptone were dissolved in deionized water, and magnetic stirring was performed for 15 minutes to slowly dissolve the solid. Subsequently, formaldehyde was slowly added to the mixed solution, and the mixture was stirred for 4 hours. The molar ratio of cobalt nitrate hexahydrate, peptone and resorcinol was 1:10:200, the molar ratio of resorcinol to deionized water was 1:27, and the molar ratio of resorcinol to formaldehyde was 1:2. Ammonia water (AR, mass concentration of 26%) was slowly added to the mixed solution under 80°C water bath conditions, the pH value of the solution was adjusted to 14, and the reaction was stirred for 120 minutes to form an organic gel. Finally, it was placed in a vacuum drying oven (vacuum degree of 133Pa), vacuum dried at 105°C for 10 days, and the obtained solid was ground to obtain metal organic gel (MOG).

[0118] The ground ZIF-67, MOG and polymethyl methacrylate were added to N,N-dimethylformamide, the mass ratio of ZIF-67 to MOG was 100:1, and the mass ratio of the total mass of ZIF-67 and MOG to polymethyl methacrylate was 10:1. The mixed solution was magnetically stirred at 100°C for 96 hours to obtain a uniformly mixed spinning solution.

[0119] 800 mL of spinning solution was placed in a syringe with a capacity of 1000 mL, and electrospun nanofibers were obtained using electrospinning technology. The electrospinning parameters were: needle voltage of 50 kV, injection rate of 10 mL / h, collection speed of 1000 rpm, round-trip distance of 180 mm, spinning temperature of 50 ° C, and spinning humidity of 60% RH. The electrospun nanofibers were placed in a vacuum drying oven and vacuum dried at 100 ° C for 48 hours to obtain nanofibers.

[0120] The nanofibers were placed in a high-temperature tube furnace and carbonized at high temperature under inert gas N2 (N2 flow rate was 200 mL / min). 3 g of urea was placed in an ark at the air inlet of the tube furnace, and the temperature was increased to 1200°C at a heating rate of 15°C / min, and carbonized at 1200°C for 12 hours. After carbonization, the obtained carbon nanocomposite material was ground and subjected to high-energy ball milling treatment to obtain the ZIF-MOG-derived composite nanocarbon fiber catalyst (ZMCF-10).

[0121] Comparative Example 1

[0122] The preparation of MOG in Example 1 was omitted, and other processes were the same as in Example 1. ZIF-67 was directly subjected to electrospinning and high-temperature treatment to obtain the nanocarbon fiber material ZCF.

[0123] The performance tests were conducted on ZMCF-1 of Example 1, ZMCF-2 of Example 2, and ZCF of Comparative Example 1: the carbon fiber material itself was subjected to AC impedance method, linear sweep voltammetry and other tests using an electrochemical workstation to determine the catalytic activity of the catalyst itself; the carbon fiber materials of Examples 1 to 2 and Comparative Example 1 were assembled into batteries, respectively, and the charge-discharge cycle and power density tests were conducted. The specific process for preparing the battery is as follows: the zinc-air battery uses a polished zinc plate as the anode, an air electrode as the cathode, and a 6MKOH solution as the electrolyte. The ratio of the ink-colored catalyst slurry is: 5 mg catalyst + 50 μL Nafion + 950 μL anhydrous ethanol. Take 200 μL of the ink-colored catalyst slurry and drop it on the nickel mesh gas diffusion layer to form a catalytic layer (effective geometric area is 1 cm 2 , the catalyst loading is 1 mg cm -2 ). Then place the zinc sheet on the anode plate, followed by the anti-dendrite diaphragm, sealing ring, liquid storage battery plate, sealing ring, air cathode, cathode battery plate, and finally install the screws, gaskets and nuts, tightening them symmetrically to ensure uniform force. Finally, connect the assembled battery to the liquid storage bottle and the circulating peristaltic pump. The assembled battery is tested for constant current charge and discharge using the Blue Electric Battery Test System.

[0124] The ORR and LSV polarization curves of ZMCF-1 of Example 1, ZIF-67 of Comparative Example 1, and Pt / C in 0.1 mol / L KOH solution are shown in FIG. Figure 1 As shown; the OER polarization curves of ZMCF-1 of Example 1, ZIF-67 of Comparative Example 1, and RuO2 in 1 mol / L KOH solution are shown Figure 2 As shown; the discharge polarization curve and power density diagram of the zinc-air battery assembled with ZMCF-1 and Pt / C as cathode catalysts in Example 1 are as follows Figure 3 As shown; the zinc-air battery and Pt / C-RuO2 battery assembled with ZMCF-1 of Example 1 as cathode catalyst at 10mA / cm 2 The constant current charge and discharge curve under Figure 4 The ORR and LSV polarization curves of ZMCF-2 and Pt / C in 0.1 mol / L KOH solution of Example 2 are shown in Figure 5 As shown; The OER polarization curves of ZMCF-2 and RuO2 in 1 mol / L KOH solution of Example 2 are shown Figure 6 shown.

[0125] like Figure 1 As shown, the half-wave potential (E 1 / 2 ) reaches 0.8 V (vs. RHE), which is almost equivalent to the half-wave potential (E 1 / 2 =0.82V), showing excellent ORR catalytic activity. Figure 2 It can be seen that at 10mA / cm 2 Under the current density, the OER overpotential of ZMCF-1 material is 396mV, which is lower than the overpotential of Z-CNF (430mV), but there is still a gap of 41mV compared with the overpotential of RuO2 (355mV). As the current density increases, the overpotential of ZMCF-1 material gradually approaches or even falls below the overpotential of RuO2. This indicates that ZMCF-1 material has good OER catalytic activity. Figure 3 It can be seen that the maximum power density of the zinc-air battery assembled with ZMCF-1 material can reach 115.7mW / cm 2 , slightly lower than the maximum power density of Pt / C-RuO2 battery 121mW / cm 2 , showing excellent battery performance. Figure 4 For batteries at 10mA / cm 2The constant current charge and discharge curves under the condition of 1.3V can be seen from the figure. The initial charge and discharge voltage range of the ZMCF battery is 1.3V, but after running for 200 hours, its charge and discharge voltage range gradually decreases and remains stable (about 1.18V). Under the same conditions, the Pt / C-RuO2 battery only runs for 85 hours, and the charge and discharge voltage range increases to 1.62V. This shows that the zinc-air battery assembled with ZMCF-1 material has excellent cycle stability. Figure 5 It can be seen that the half-wave potential (E 1 / 2 ) reaches 0.78 V (vs. RHE), which is close to the half-wave potential (E 1 / 2 =0.82V), showing excellent ORR catalytic activity. Figure 6 It can be seen that at 10mA / cm 2 Under the current density, the OER overpotential of ZMCF-2 material is 400mV, which is 45mV lower than the overpotential of RuO2 (355mV). However, as the current density increases, the overpotential of ZMCF-2 material gradually approaches and is lower than the overpotential of RuO2, indicating that ZMCF-2 material exhibits good OER catalytic activity.

[0126] The results of the embodiments show that the ZIF-MOG derived composite carbon fiber (ZMCF) material prepared by the present invention accelerates the kinetic process of oxygen reduction (ORR) and reduces the overpotential of the oxygen evolution (OER) reaction. After long-term charge and discharge cycles, the voltage range remains stable without obvious attenuation, and has broad development prospects.

[0127] The present invention combines zeolite imidazole framework (ZIF-67) with metal organic gel (MOG), and uses electrostatic spinning technology to achieve microscopic composite of the two at the nanoscale, forming a nanofiber network structure, while enhancing the conductivity of the material itself, it also exposes more active sites, and then undergoes high-temperature carbonization and heteroatom doping, high-energy ball milling and other forms to further improve the conductivity and catalytic activity of the material itself, establish the advantages of one-dimensional ZIF gel co-doping, increase active sites, and improve the conductivity and electrochemical activity of nanofibers. The present invention is of great significance for preparing a new high-performance non-precious metal bifunctional catalyst, improving the conductivity and high electrocatalytic activity of the catalyst, further improving the power density and charge and discharge efficiency of zinc-air batteries, and then promoting the industrialization development of zinc-air batteries.

[0128] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a ZIF-MOG derived composite nanocarbon fiber catalyst, characterized in that: The following steps are included: 1) mixing dimethylimidazole, a metal salt and an organic solvent and reacting them to obtain ZIF-67; 2) mixing the metal salt, the nitrogen-containing component, resorcinol and water to obtain a mixed solution, and sequentially adding formaldehyde and ammonia water to the mixed solution to react and form a metal organic gel; 3) mixing ZIF-67, metal organic gel, nanofiber polymer and solvent to obtain a spinning solution; 4) The spinning solution is electrospun and dried sequentially to obtain nanofibers; 5) The nanofibers are sequentially subjected to high temperature carbonization and refinement treatment to obtain a ZIF-MOG derived composite nanocarbon fiber catalyst.

2. The preparation method according to claim 1, characterized in that: Step 1) The organic solvent is ethanol, N,N-dimethylformamide or methanol, and the metal salt is iron salt, cobalt salt, nickel salt, copper salt or zinc salt; The molar ratio of the metal salt to dimethylimidazole is 1:8-80, and the molar ratio of dimethylimidazole to the organic solvent is 1:16-160; The reaction temperature is 15-80° C., and the reaction time is 2-48 hours.

3. The preparation method according to claim 1 or 2, characterized in that: Step 2) the metal salt is an iron salt, a cobalt salt, a nickel salt, a copper salt or a zinc salt; the nitrogen-containing component is peptone, melamine, urea or chitosan; The reaction time is 5 to 120 minutes, the reaction temperature is 30 to 140° C. Ammonia water is added to make the pH value of the system 7 to 14.

4. The preparation method according to claim 3, characterized in that: Step 2) The molar ratio of the metal salt, the nitrogen-containing component and resorcinol is 1:1-10:20-200, the molar ratio of resorcinol to formaldehyde is 1:1-3, and the molar ratio of resorcinol to water is 1:25-30.

5. The preparation method according to claim 1, characterized in that: Step 3) the nanofiber polymer comprises polyacrylonitrile, polyvinyl pyrrolidone, polyvinyl alcohol, polystyrene or polymethyl methacrylate; the molecular weight of polyacrylonitrile is 50,000 to 300,000, and the solvent comprises water, N,N-dimethylformamide, methanol or ethanol; The mixing temperature is 20-100° C., and the mixing time is 6-96 hours.

6. The preparation method according to claim 4 or 5, characterized in that: Step 3) The mass ratio of the ZIF-67 to the metal organic gel is 1-100:1-100, and the mass ratio of the total mass of the ZIF-67 and the metal organic gel to the nanofiber polymer is 1-10:1-10.

7. The preparation method according to claim 6, characterized in that: Step 4) The process parameters of the electrospinning are: the voltage of the needle is 5-50 kV, the injection rate is 0.1-10 mL / h, the collection speed is 200-1000 rpm, the round-trip distance is 60-180 mm, the spinning temperature is 10-50 ° C, the spinning humidity is 10-60% RH; the drying temperature is 40-100 ° C, and the drying time is 2-48 h.

8. The preparation method according to claim 1 or 7, characterized in that: Step 5) The temperature of the high-temperature carbonization is 650-1200°C, the time of the high-temperature carbonization is 1-12h, and the heating rate of the high-temperature carbonization is 2-15°C / min; the high-temperature carbonization is carried out under a protective gas atmosphere, and the flow rate of the protective gas is 10-200mL / min.

9. The ZIF-MOG derived composite nanocarbon fiber catalyst prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the ZIF-MOG derived composite nanocarbon fiber catalyst in a battery according to claim 9, characterized in that: The battery is a battery in which oxygen participates in the cathode reaction.

Citation Information

Patent Citations

  • Guanosine supramolecular metal organic gel / MOF composite material as well as preparation method and application thereof

    CN111647164A

  • Bead-like cobalt-nitrogen co-doped carbon nanocage / carbon nanofiber composite catalyst and preparation method thereof

    CN114420958A

  • Iron-cobalt bimetal oxygen reduction electro-catalytic material as well as preparation method and application thereof

    CN114843536A

  • Preparation method and application of iron-cobalt doped porous carbon nanofiber

    CN116666657A

  • Metal organic carbon composite catalyst and synthesis method thereof

    CN117199404A